The impact of smoking on response to tumor necrosis factor-α inhibitor treatment in patients with ankylosing spondylitis - (:unkn) unknown (My University, 2023)
Background/aim: To investigate the impact of smoking on disease activity, treatment retention, and response in patients with ankylosing spondylitis (AS) treated with their first tumor necrosis factor-α inhibitor (TNFi). Materials and methods: AS patients who started their first TNFi treatment for the active axial disease (BASDAI ≥ 4) from TURKBIO Registry were included. Treatment response of smoker (current and ex-smokers) and nonsmoker (never smoker) patients were primarily evaluated as achievement of BASDAI50 or improvement in BASDAI at least 20 mm at 3 months and 6 months compared to baseline. Results: There were 322 patients with AS (60% male, 59% smoker, mean age: 38.3 years). The median follow-up time was 2.8 years (Q1– Q3: 1.3–3.8), and disease duration was 3.5 years (Q1–Q3: 0.7–8.2). Smokers had male predominance (p < 0.001), lower ESR (p = 0.03), higher BASDAI (p = 0.02), BASFI (p = 0.05), HAQ-AS (p = 0.007), and ASDAS-CRP (p = 0.04) compared with nonsmokers at baseline. In the multivariate analysis, male gender [OR 2.7 (95%CI 1.4–5), p = 0.002], and concomitant conventional synthetic disease-modifying antirheumatic drug use [OR 2.4 (95%CI 1.1–5.2), p = 0.03] were associated with better treatment response. There was an association of male gender [HR 2.4 (95%CI 1.6–3.7), p < 0.001], older age (≥30years) [HR 1.8 (95%CI 1.1–2.8), p = 0.01], and response to treatment [HR 1.8 (95%CI 1.2–2.9), p = 0.008] with better treatment retention. No impact of smoking status was found on treatment retention and response in univariate and multivariate analyses. Conclusion: This study suggested that smoking was associated with poorer patient-reported outcomes in biologic naïve AS patients initiating their first TNFi treatment, but it had no impact on the TNFi treatment response and retention rate.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Ankylosing spondylitis; registry; smoking; treatment response; tumor necrosis factor-alpha inhibitor; Ankylosing spondylitis; smoking; tumor necrosis factor-alpha inhibitor; treatment response; registry